Premiums diversity of group pension fund based on the aggregate cost method - Aprijon,; Azmin Sham Rambely,; Saiful Hafizah Jaaman, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Participants can withdraw pension fund insurance before reaching the normal retirement age due to factors such as death, permanent disability, or early retirement. As a result, the participant's premium payment differs from what they would pay in retirement. The aggregate cost method is one of the methods used to calculate pension contributions. The purpose of this study is to determine the current value of pension benefits and insurance premiums based on uniform assumptions using the aggregate cost method. This calculation method is based on common characteristics that are influenced by the amount of salary and the rate of increase of the insured salary while working. The results showed that male participants received more pension benefits than female participants, who received the same salary, salary increase rate, and entry age. Meanwhile, male participants paid higher premiums than female participants.